An Hybrid Novel Layered Architecture and Case Study: IoT for Smart Agriculture and Smart LiveStock - HOUNGUE, Yénukunmè Pélagie Elyse; SAGBO, Romaric Kouessi Arafat; KEDOWIDE, Colombiano (My University, 2020)
The meteoric rise in the number of connected objects in our daily lives is proof that data transmission and improvement of services related to our activities are a permanent and urgent concern. Communicating objects transform our behaviors, our habits and our society in general. Despite the significant progress in the field of Internet of Things (IoT), much remains to be done especially in developing countries. In the field of e-agriculture, digital production techniques are not enough to guarantee a better yield and safeguard crops. Thus, in this work, we have focused on the resolution of the problems related to transhumance, given the expansion of the phenomenon in developing countries. Indeed, during transhumance, passages intended for animals, called corridors may not be followed by the breeders. This can lead to deadly clashes between herders and farmers. Our vision is to help through the implementation of a smart guidance system based on IoT Technologies, herders to better control their livestock following the predefined corridors from north to south of Benin and vice versa. In order to help farmers to save their crops in case of flood, our system will integrate a prediction module that will enable them to anticipate natural events such as flooding in the heavy rainy season. In this paper, our researches will therefore focus on the proposal of a multi-level architecture that can enable us to achieve the aforementioned objectives.
Keywords: IoT · Smart · Prototype · Sensors · E-agriculture ·; Smart-village · Livestock · Farmer · Big data